Evaluasi performa reproduksi sapi perah Friesian Holstein pada laktasi pertama di PT. Ultra Peternakan Bandung Selatan - Raden Febrianto Christi; Didin S Tasripin; Arin Rinaldi (Composite : Jurnal Ilmu Pertanian, 2021)
Reproduction management is one of the important things in a dairy farming business because good reproductive management, along with high reproductive capacity, will increase the efficiency and productivity of livestock. This study aims to determine the reproductive performance of FH dairy cows at first lactation on first mating post partus, service per conception, days open, calving interval, coception rate, calving rate and fertility status. The results of the research showed reproductive performance with parameters first mating post partus 59.5 days, service per conception 4.5 times, days open 145,5 days. The conclusion of this research is reproductive performance is not optimal.